2016
DOI: 10.1259/dmfr.20150162
|View full text |Cite
|
Sign up to set email alerts
|

Cervical vertebrae maturation index estimates on cone beam CT: 3D reconstructions vs sagittal sections

Abstract: Although CBCT imaging must not be used exclusively for this purpose, it may be suitable for skeletal maturity assessments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
1
7
0
1
Order By: Relevance
“…These findings are in accordance with Hariharan et al (11) , Bonfim et al (12) , Cassetta et al (13) who found that linear and angular measurements from CBCT were similar to measurements from conventional lateral cephalogram. It is important to note that none of these studies used the synthesized two dimensional images from CBCT, nor did any studied cleft patients.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are in accordance with Hariharan et al (11) , Bonfim et al (12) , Cassetta et al (13) who found that linear and angular measurements from CBCT were similar to measurements from conventional lateral cephalogram. It is important to note that none of these studies used the synthesized two dimensional images from CBCT, nor did any studied cleft patients.…”
Section: Discussionsupporting
confidence: 91%
“…A C2-es csigolya tekintetében nemigen sikerült kapcsolatot kimutatni, amit azzal magyaráztak, hogy a 2. nyaki csigolya hajlamos a leginkább a remodellálódásra a növekedés folyamán. Több szerző is egyetért abban, hogy a CBCT-felvételekből készített 2D, sagittalis metszeti felvételek és a csigolyákról készült 3D-rekonstrukciók is ugyanolyan jól alkalmazhatók, mint az oldalirányú teleröntgenek [10,31]. Eszerint bármely klasszikus csigolyavizsgálati analízis szempontrendszerét felhasználva ugyanolyan pontos megbízhatósággal meghatározhatunk csontérettséget a 3D-felvételeken is.…”
Section: Háromdimenziós (3d) Képalkotó Eljárásokra éPülő Vizsgálómódsunclassified
“…Hand-wrist and CVM methods were used for assessing the adolescent growth peak. It is suggested that the CBCT images may be useful for estimates of skeletal maturation, although they should not be used solely for that purpose [65]. Shim et al [66] claimed that the esti- Cone Beam Computed Tomography in Orthodontics http://dx.doi.org/10.5772/intechopen.68555 mate of maturation stages of the cervical vertebrae on CBCT provided a reliable evaluation of pubertal growth support and strongly positive correlations with lateral cephalograms and hand-wrist radiographs.…”
Section: Evaluation Of Cervical Vertebral Maturation (Cvm)mentioning
confidence: 99%